Factors influencing the internet banking adoption decision in North Cyprus: An evidence from the partial least square approach of the structural equation modeling - Hiba Alhassany; Faisal Faisal (Financial Innovation, 2018)
Purpose: This paper aims to examine how the adoption decision of the internet banking in North Cyprus would be affected based on the following dimensions; the technology features, the personal characteristics, the social environment and the expected risk. Design/methodology/approach: A self-administered survey was conducted with 291 participants responded to it. The partial least square approach of the structural equation modeling (PLS-SEM) is employed to investigate the direct effects of the proposed factors on the adoption decision. Additionally, the mediation test is used to examine indirect effects. Findings: Results showed that even though the participants appreciated the benefits of the online banking as the perceived usefulness factor exerts the greatest direct effect, they would rather use clear and easy-to-use websites, adding to that their assessments of the usefulness of these services are significantly influenced by the surrounding people's views and prior experience. This is demonstrated by the total effects of the perceived ease of use and the subjective norm factors, which are greater than the direct effect of the perceived usefulness factor since both of these factors have significant direct and indirect effects mediated by the perceived usefulness factor. The negative impact of the perceived risk factor is weak compared to the previous factors. While the personal innovativeness factor showed the weakest effect among the proposed factors.
Keywords: 650; Behavioral theories; Technology adoption; TAM; Subjective norm; Personal innovativeness; Perceived risk; Partial least square; Structural equation modeling